2002
DOI: 10.1200/jco.2002.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use Among Adult Cancer Survivors: Analyses of the National Health Interview Survey

Abstract: Cancer seems to be one of several chronic illnesses that precipitates the need for and use of mental health services. Improvements are needed in recognizing mental health problems among cancer survivors and reducing barriers to psychosocial service use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
3
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(161 citation statements)
references
References 24 publications
9
145
3
4
Order By: Relevance
“…8 In addition, an American study reported that cancer survivors contacted a mental health provider in 7% of cases. 9 In our study, the percentage of patients who visited a psychologist was positively related to a higher educational level. To our knowledge, this effect has not been described before for cancer patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…8 In addition, an American study reported that cancer survivors contacted a mental health provider in 7% of cases. 9 In our study, the percentage of patients who visited a psychologist was positively related to a higher educational level. To our knowledge, this effect has not been described before for cancer patients.…”
Section: Discussionmentioning
confidence: 64%
“…8 Moreover, cancer survivors reported a greater need for mental health services than individuals without a history of cancer, especially those who were under the age of 65 and diagnosed at a younger age, were formerly married, or had other comorbid chronic conditions. 9 The difference in health care utilization between long-term cancer survivors and the general population could not be attributed to the higher prevalence of common somatic complaints. Cancer-related health issues might explain the increase in use of health care.…”
mentioning
confidence: 99%
“…23,24 We found a substantial symptom burden among cancer survivors compared with general population controls, with the greatest difference seen in patients younger than 50. Previous literature has found that younger survivors were more likely to report psychosocial problems and use mental health services compared with older survivors, 24,25 and our study helps quantify this magnitude by comparing cancer survivors with the general population in the specific age categories. A number of reasons can account for why symptom burden may be greater among younger survivors.…”
Section: Discussionmentioning
confidence: 86%
“…A presença de dor e o uso de terapias antineoplásicas (interferon, quimioterapia) são fatores de risco, além de dificultarem a identificação da depressão, que ainda permanece um desafio para o médico que atende pacientes com câncer. A depressão, por sua vez, aumenta o uso de serviços de saúde mental, interfere negativamente com a adesão aos tratamentos do câncer e com a qualidade de vida dos pacientes 5,6 . Os benefícios do uso de antidepressivos na depressão em pacientes com câncer estão bem estabelecidos na literatura.…”
Section: Introductionunclassified